PENERAPAN METODE AL-MIFTĀH LIL ‘ULŪM DI PONDOK PESANTREN DARUL AMIEN KECAMATAN DAHA UTARA KABUPATEN HULU SUNGAI SELATAN - jamilah, Nor; Zainuddin; Jazuli, Sulaiman (IAI DARUL ULUM KANDANGAN, 2025)
Studying or reading yellow books, such as the writings of the Salafus Salih requires an understanding of Arabic, Nahwu, Sharaf and a method that is considered effective, namely al-miftāh lil ‘ulūm. This modern method is included because it is considered that the habit of using traditional methods needs improvement. The purpose of this study is to determine the application of the al-miftāh lil ‘ulūm method at the Darul Amien Islamic Boarding School, Daha Utara District, Hulu Sungai Selatan Regency and the factors that influence it. This type of research is field research, this research refers to the entire group that is the focus of the study, namely all individuals who are directly involved with the Al-miftāh lil ‘ulūm method, the focus is the application of the Al-miftāh lil ‘ulūm method at the Darul Amien Islamic Boarding School, Daha Utara District, Hulu Sungai Selatan Regency and the factors that influence it. Data collection techniques are observation, interviews, and documentation. Data analysis is qualitative analysis, which begins with data collection, selecting the required data, data presentation, and ending with conclusions. This study shows that the application of the Al-miftāh lil ‘ulūm method uses a planning stage, namely determining learning objectives, teaching materials, achievement targets, and compiling evaluation tools, then the implementation stage uses several methods, namely the method of understanding, memorizing, question and answer, the song learning method while using the five-finger method, and the innovative game method, as well as the assessment stage, namely written tests and oral tests. The innovation of this method is influenced by teachers and the motivation of students who can help them more easily understand the yellow book and improve the quality of Islamic boarding school education with adequate facilities and infrastructure.